2020
DOI: 10.3847/2041-8213/ab88b6
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic X-Ray Jets from the Black Hole X-Ray Binary MAXI J1820+070

Abstract: The black hole MAXIJ1820+070 was discovered during its 2018 outburst and was extensively monitored across the electromagnetic spectrum. Following the detection of relativistic radio jets, we obtained four Chandra X-ray observations taken between 2018 November and 2019 June, along with radio observations conducted with the Very Large Array and MeerKAT arrays. We report the discovery of X-ray sources associated with the radio jets moving at relativistic velocities with a possible deceleration at late times. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(89 citation statements)
references
References 36 publications
7
82
0
Order By: Relevance
“…Unfortunately, there have been no published radio measurements of the synchrotron break to independently estimate the radius and distance of the jet ejecta, but this distance is reasonable, when compared to the BHB MAXI J1535-571 where the emission height above the black hole is ∼ 10 8 R g (Russell et al 2020). We also note that recent Chandra imaging showed a transient X-ray jet ejecta at the time of the radio flare, inferring that the ejecta was a cone of 1.5 × 10 4 au by 7.7 × 10 3 au (Espinasse et al 2020). As 1 au ∼ 10 7 R g for a 10 M e black hole, this would lead to a vertical extent of the transient jet emitting in X-ray of ∼10 11 R g , and the light travel distance of several days is always below this upper limit.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Unfortunately, there have been no published radio measurements of the synchrotron break to independently estimate the radius and distance of the jet ejecta, but this distance is reasonable, when compared to the BHB MAXI J1535-571 where the emission height above the black hole is ∼ 10 8 R g (Russell et al 2020). We also note that recent Chandra imaging showed a transient X-ray jet ejecta at the time of the radio flare, inferring that the ejecta was a cone of 1.5 × 10 4 au by 7.7 × 10 3 au (Espinasse et al 2020). As 1 au ∼ 10 7 R g for a 10 M e black hole, this would lead to a vertical extent of the transient jet emitting in X-ray of ∼10 11 R g , and the light travel distance of several days is always below this upper limit.…”
Section: Discussionsupporting
confidence: 57%
“…MAXI J1820+070 is one of the brightest BHBs detected so far, and has exhibited a great amount of activity in radio (Bright et al 2020;Homan et al 2020), NIR (Sánchez-Sierras & Muñoz-Darias 2020), optical (Muñoz-Darias et al 2019;Paice et al 2019;Shidatsu et al 2019;Veledina et al 2019), ultraviolet (UV; Kajava et al 2019), and X-ray (Buisson et al 2019;Kara et al 2019;Espinasse et al 2020;Wang et al 2020b;Buisson et al 2021;You et al 2021;Zdziarski et al 2021). In the hard state, reverberation analysis using the Neutron Star Interior Composition Interior Explorer (NICER; Gendreau et al 2016) showed that while the broad iron line profile remained constant (and only the narrow component decreased), the frequency range where the (soft) reverberation lag dominated increased (Kara et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The motion of RK1 was monitored for ∼300 d and, after a first phase in which it travelled at a constant speed, it appeared to rebrighten while being strongly decelerated in the second phase of its motion. Decelerating discrete ejecta have been observed in a number of other sources, namely XTE J1550-564 ), H1743-322 (Corbel et al 2005, XTE J1752-223 (Yang et al 2010;Miller-Jones et al 2011), MAXI J1535-571 (Russell et al 2019a) and MAXI J1820+070 (Bright et al 2020;Espinasse et al 2020). For some of them, the discrete knots were detected both in radio and X-rays, with the Chandra observatory.…”
Section: Late Time Behaviour Of the Discrete Ejectamentioning
confidence: 96%
“…The ejected components can travel unseen for months to years, before they are detected again at large (∼pc) scales, with the emission coming from their interaction with the surrounding interstellar medium (ISM). Notably, discrete jets have been simultaneously detected at large scales in radio and X-rays for XTE J1550-564 Kaaret et al 2003;Tomsick et al 2003;Migliori et al 2017), H1743-322 (Corbel et al 2005) and MAXI J1820+070 (Espinasse et al 2020), with a broadband power-law spectrum suggesting the synchrotron nature of the emission coming from the shock region.…”
mentioning
confidence: 99%
“…The variability in MAXI J1820+070 analysed here occurs close to but distinct in time to several other features in the state change. There may be some association with the jet: around 1 day before the flaring variability, there is a jet ejection coincident with a type B QPO (Bright et al 2020;Espinasse et al 2020;Homan et al 2020). The flaring is too late to be directly associated with the ejection but could represent settling from the post-ejection state to an equilibrium.…”
Section: Discussionmentioning
confidence: 99%